ICAT inhibits glioblastoma cell proliferation by suppressing Wnt/β-catenin activity. Issue 1 (1st February 2015) - Zhang, Kailiang; Zhu, Shanjun; Liu, Yanwei; Dong, Xiaoqun; Shi, Zhendong; Zhang, Anling; Liu, Chaoyong; Chen, Luyue; Wei, Jianwei; Pu, Peiyu; Zhang, Jianning; Jiang, Tao; et al.
Highlights ICAT is downregulated in high-grade glioma samples. ICAT restoration inhibits glioblastoma cell proliferation, invasion and induces glioblastoma cell apoptosis. ICAT regulates Wnt/β-catenin signaling. Therapeutic potential of ICAT in a glioblastoma xenograft model. ICAT correlates with IDH1 mutation and TCGA subtype.